May dexpanthenol, platelet-rich plasma, and thymoquinone provide new hope to maintain liver regeneration after partial hepatectomy? - Aydın, Oktay; Pehlivanlı, Faruk; Karaca, Gökhan; Aydın, Gülçin; Altunkaya, Canan; Bulut, Huri (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Complete liver regeneration may not always be possible after liver injuries and/or partial liver resection. The present study investigated the effects of dexpanthenol, platelet-rich plasma (PRP), and thymoquinone on liver regeneration in rats after partial hepatectomy (PH).Materials and Methods: A total of 34 Wistar albino rats, each weighing 250-280 g, were randomly separated into four groups. PH was performed, and except for the control group, intraperitoneal dexpanthenol, PRP, or thymoquinone was administered to the relevant groups for 7 days. All rats were then sacrificed, and the liver tissues were examined histopathologically and biochemically.Results: PRP reduced all oxidant-antioxidant parameters in rats that experienced liver regeneration, but did not create histopathological improvement in the liver tissue. Dexpanthenol had a histopathological improving effect on the liver tissue, but had no effect on biochemical parameters. Thymoquinone showed no histopathological or biochemical effects on liver regeneration.Conclusion: Although dexpanthenol did not affect biochemical oxidative parameters, it was considered to have improving effects on liver regeneration histopathologically. In addition, it was thought that PRP may be used for treatment of ischemia-reperfusion injury and cholestatic damage of the liver. Nevertheless, further studies are required on these subjects.